Studi Penurunan Chemical Oxygen Demand (COD) Pada Air Limbah Domestik Buatan Menggunakan Biofilter Aerob Tercelup dengan Media Bioring - Marieta Sarahrut Dayanti; Netti Herlina (Universitas Andalas, 2018)
The purpose of this research is to know the effect of debit variation on Chemical Oxygen Demand (COD) reduction efficiency in artificial domestic wastewater after being processed using aerobic biofilter reactor. The biofilter was maintained at continues flow and aerobic state. The debit variations used were 0.56 l/h for 72 hours retention time, 0.83 l / h for 48 hours retention time and 1.67 l/h for a 24 hour retentione time. Efficiency of COD decreased at 0.56 l/hr variation was 84%, at 0.83 l / h was 86% while at 1.67 l/h was 75%. The effluent of domestic wastewater treatment using aerobic biofilter with bio ring media has fulfilled the Minister of Environment and Forestry Regulation No. 68/2012 on Quality Standard of Domestic Wastewater.